1999
DOI: 10.1038/sj.jp.7200210
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Amniotic Fluid Markers of Intra-Amniotic Infection With Histopathology in Cases of Preterm Labor With Intact Membranes

Abstract: OBJECTIVE:To evaluate the correlation of amniotic fluid (AF) markers (AFMs) of intra-amniotic infection with histopathologic findings in cases of preterm labor with intact membranes, between 22 and 36 weeks' gestation. STUDY DESIGN:We reviewed the charts of patients admitted in preterm labor with intact membranes between January 1993 and December 1996. Those having amniocentesis were identified, and AFMs were compared with histopathology in patients who delivered within 48 hours of the amniocentesis. The AFMs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 8 publications
(14 reference statements)
1
14
0
1
Order By: Relevance
“…Several investigators have reported that the incidence of intra-amniotic inflammation (as assessed by a mass-restricted score or glucose level) was significantly higher in patients with HCA than in those without HCA, all of whom delivered within 48 hours of amniocentesis [9, 18]. In accordance with previous reports [9, 18], our results demonstrated that women with HCA who had negative AF culture results showed stronger intra-amniotic inflammatory response (elevated AF IL-6, IL-8, and MMP-9 levels) and a higher rate of intra-amniotic inflammation than those without HCA with negative AF culture.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported that the incidence of intra-amniotic inflammation (as assessed by a mass-restricted score or glucose level) was significantly higher in patients with HCA than in those without HCA, all of whom delivered within 48 hours of amniocentesis [9, 18]. In accordance with previous reports [9, 18], our results demonstrated that women with HCA who had negative AF culture results showed stronger intra-amniotic inflammatory response (elevated AF IL-6, IL-8, and MMP-9 levels) and a higher rate of intra-amniotic inflammation than those without HCA with negative AF culture.…”
Section: Discussionmentioning
confidence: 99%
“…Chorioamnionitis was present in 60% of deliveries arising from pPROM and 40% of deliveries following preterm labor. Chorioamnionitis has previously been associated with 36 -60% of placentas resulting from preterm labor with intact membranes (14,16,47) compared with 42-80% of placentas after pPROM (15,45,48). Only a proportion of cases of chorioamnionitis have been associated with microbes isolated from either placenta (14) or amniotic fluid (16).…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies associating direct and indirect evidence of intra-amniotic infections and spontaneous PTD [57][58][59][60][61] . The microorganisms that have been implicated include bacterial vaginosis, group B streptococcus, trichomonas vaginalis, mycoplasmas, fusobacteria and Ureaplasma urealyticum.…”
Section: Infection and Preterm Deliverymentioning
confidence: 99%